7 P38γ mitogen-Activated Protein Kinase is a Mediator of Pathological Cardiac Hypertophy. (19th January 2014) - Thomas, M; Uddin, S; Loonat, A; Marber, M; Clark, J
Abstract : Pathological cardiac hypertrophy is a fundamental component of the remodelling process following myocardial infarction that ultimately culminates in heart failure. p38-mitogen activated protein kinases (p38-MAPKs, of which there are 4 isoforms; α, β, γ and δ) are serine/threonine kinases that are activated in response to stress. Classically, studies have examined the role of the most abundant p38α isoform. However, it is now apparent that p38γ is also highly expressed in the myocardium. There is evidence to support its role in skeletal muscle differentiation and growth but little is known about its role in the heart. Our hypothesis is that this isoform of p38 has a key role in the induction of cardiac hypertrophy. We have previously demonstrated that p38γ knockout (KO) mice are resistant to pathological cardiac hypertrophy. In this study we investigated the expression, activation and localisation of p38γ, its substrates and activation in the myocardium on normal and hypertrophic mouse hearts. Using surgical and pharmacological induction of pathological hypertrophy in wild type and p38γ KO mice, we used cardiac ultrasound (to assess cardiac function and ventricle morphology), immunohistochemistry and immunoblotting to look at expression, activation and localisation of hypertrophic markers, p38 kinases and potential substrates and interacting partners of p38γ in the myocardium. In this study we have demonstrated translocation of p38γ from the intercalated disks (and cell membrane) to the nucleus of myocytes and identified potential interacting proteins within the heart. This evidence will help identify the role of this kinase in the progression of pathological hypertrophy.